Вестник любви: журнал В. А. Жуковского в истории русской лирики - Vinnickij, Il'ja (Wiener Slawistischer Almanach, 2023)
The role of the editor in the formation of the politics, content, and rhetorical tone (emotional mode) of an eighteenth and early nineteenth century Russian journal was enormous. In this article, I will focus on the techniques of lyrical personification (“a secret history of editor’s love” under the mask of essays by various writers) of a literary and political journal edited by one of the founders of Russian Romanticism. I consider these techniques within the context of the history of the early Russian Romantic movement, itself deeply affected by German literary and journalistic tradition of the late eighteenth century.